Gamified flipped classroom in education: a systematic review - Wan Masitah Wan Majid; Farah Mohamed Zain; Siti Noor Ismail (Institute of Advanced Engineering and Science, 2024)
Nowadays, gamified flipped classrooms (GFC) are a cutting-edge teaching method. Using gamification techniques with flipped classrooms (FC) significantly positively affects teachers and students. This study reviews the impact of GFC research on education methodically. Hence, the study investigated a comprehensive literature review of 52 empirical research publications published between 2018 and 2022 in various electronic databases and on the web. Note that the review established the foundation for the significance of upcoming research projects by critically assessing and evaluating the different inconsistencies in the literature. In addition to examining the contradictory results of previous research, the study offer a framework as well as guidance for future researchers in terms of theoretical models, methodology, game tools or online platforms, game activity, game elements, variables, and the impact of a GFC.